Effects of asymmetrical exercise demands on the symmetry of skin temperature in archers. (3rd December 2020) - Sanchis-Sanchis, Roberto; Priego-Quesada, Jose Ignacio; Ribas-Garcia, Vicent; Carpes, Felipe P; Encarnacion-Martinez, Alberto; Perez-Soriano, Pedro
Abstract: Objective : To analyse skin temperature asymmetries in response to asymmetrical exercise demand in archers. Approach : The skin temperature of the trunk and upper limbs was measured in 30 archers with an infrared camera at three different moments: before (Pre), immediately after (Post), and 10 min after (Post10 ) a simulated competition (18 warm-up shots and 72 qualifying round shots). Relative and absolute asymmetries were determined. Stepwise multiple linear regressions were performed using the variations of relative and absolute skin temperature asymmetries as predicting variables, and sex, age, experience, body mass index, bow mass, bow power, and rate of perceived exertion of competition as inputs. Main results : Relative symmetry values were lower, i.e. more negative values indicating more asymmetry (higher skin temperature on the bow side, p < 0.05 and ES > 0.5) in the Post than in the Pre moment in the upper back (95% CI [0.1, 0.4 °C]), posterior shoulder (95% CI [0.0, 0.5 °C]), posterior arm (95% CI [0.0, 0.6 °C]) and posterior elbow (95% CI [0.4, 0.9 °C]). Absolute asymmetries were higher ( p < 0.01 and ES > 0.8) in the Post than in the Pre moment in the chest (95% CI [0.1, 0.4 °C]), upper back (95% CI [0.1, 0.3 °C]), posterior shoulder (95% CI [0.1, 0.5 °C]) and posterior elbow (95% CI [0.2, 0.7 °C]). The variation of asymmetries after competition could be explained by factors such as experience, effort perception, sex, and bow mass. Significance : Archery exercise results in skin temperature asymmetry related to higher temperature in the bow side, which plays a main role in sustaining muscle activation to keep position. The asymmetry characteristics may result from the archery technique.